The singularity within the school organization. Forgotten heritage of the historical Institutes - Pérez-Dionis Chinea, David (Avances en Supervisión Educativa, 2010)
In 1845 the plan known as Pidal meant the withdrawal of most of the universities and the establishment of the Provincial Schools of Secondary Education. These educational institutions inherited in most of the cases the movable and immovable items of the ancient university establishments. The Pidal plan also established a whole equipment of the scientific laboratories of these schools. The present heirs of the most ancient schools in our country still preserve most of these elements that together with the artistic, bibliographic and documentary items or even the own buildings that are home to them, constitute the Historic and Educational Patrimony. During the last years a series of initiatives such as the celebration of national conferences or the creation of the National Group of Historic Secondary Schools has highlighted the pressing need of an involvement from the different educational administrations in the huge and hardly acknowledged work of the teachers in charge of the restoration, cataloguing and care of this rich patrimony.